Self-Efficacy In Entrepreneurship As A Mediator Between Industrial Work Practice And Entrepreneurship Education - Imaniyah, Sari Ayu; Heri Pratikto; Ludi Wishnu Wardana (International Journal of Business and Quality Research, 2025)
This study aims to analyze the effect of the Double Track Program and entrepreneurship education on the entrepreneurial readiness of high school students in Sumenep Regency, with entrepreneurial self-efficacy as a mediator. The problem raised is the low level of entrepreneurial readiness despite participating in entrepreneurship programs. The research method used a quantitative approach with data collection through questionnaires on 238 student respondents and data analysis using SEM-PLS. The results of the analysis show that the Double Track Program and entrepreneurship education have a significant effect on entrepreneurial readiness, and entrepreneurial self-efficacy mediates this relationship. In conclusion, strengthening entrepreneurial self-efficacy is important to improve the effectiveness of the program and students' readiness for entrepreneurship